Self-leveling fireproof anti-condensation plugging high polymer material and preparation method thereof
By combining the self-leveling fire-resistant and anti-condensing polymer materials with components such as vinyl siloxane, hydrogen-containing silicone oil and flame retardant fillers, the problem that existing sealing materials cannot effectively prevent flames and moisture in high-temperature environments is solved. The self-leveling time of the material is controlled and efficient fire-proof, moisture-proof and earthquake-resistant, and the sealing effect and durability are enhanced.
Patent Information
- Application Number
- CN202310846796.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-11
- Publication Date
- 2025-01-14
AI Technical Summary
The existing sealing materials cannot effectively prevent the passing of flames, flue gas, toxic gas, moisture and liquid water in high-temperature environments, and have poor durability after curing, which cannot adapt to complex environments and real-time allocation needs, resulting in frequent safety hazards and maintenance.
Use self-leveling fire-resistant and anti-condensing polymer materials composed of components A, B, and C. Component A includes vinyl siloxane, catalyst, reinforcement and flame retardant filler. Component B includes hydrogen-containing silicone oil and anti- The condensate hydrophobic filler, component C is a leveling agent, which controls the self-leveling time and curing speed through the assembly distribution ratio to enhance the fire, moisture and earthquake resistance of the material.
It realizes the self-leveling time of the material, excellent flame retardancy and bonding strength, good sealing effect, reduces condensation generation, has good fire resistance, moisture resistance and earthquake resistance, is not easy to age, can prevent flame spread and reduce flames at high temperatures Combustion temperature.
Smart Images

Figure CN119307098A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of plugging materials, and in particular relates to a self-leveling fireproof and anti-condensation polymer material and a preparation method thereof. Background Art
[0002] With the development of science and technology and the rapid progress of urbanization, the requirements for safe and stable operation of power grids are getting higher and higher. In power operations, in common substation equipment such as ring network cabinets, box transformers, and cable branch boxes, when the ambient temperature rises, due to thermal inertia, the temperature of the equipment surface is lower than the internal ambient temperature. If the surface temperature of the equipment is relatively low, water vapor will condense on the surface to form dew drops, causing creepage and flashover accidents, and the requirements for fire prevention in power work are getting higher and higher;
[0003] The existing traditional method is to use fireproof mud for sealing, but fireproof mud is cheap, easy to solidify and crack, and has poor fixed sealing durability. It cannot effectively prevent the passage of flames, smoke, toxic gases, moisture, liquid water, and small animals. Once a fire occurs, flames, smoke, and toxic gases pass through holes and gaps, which will cause huge personal safety hazards. It has poor durability and requires frequent maintenance. Problems will occur in a short period of time and the sealing effect will be lost. The existing sealing method cannot adapt to the complex outdoor environment, cannot be deployed in real time, and cannot well control the time of self-leveling. Summary of the invention
[0004] In view of the deficiencies of the prior art described above, the purpose of the present invention is to provide a self-leveling fireproof and anti-condensation polymer material, which can provide better blocking effect, controllable leveling, good moisture-proof, fireproof and earthquake-resistant effects, and is not easy to age; To achieve the above-mentioned purpose of the invention, the present invention provides the following technical solutions: A self-leveling fireproof and anti-condensation polymer material, composed of components A, B, and C; component A is composed of the following components in parts by weight: 40 to 50 parts of vinyl siloxane, 1 to 3 parts of catalyst, 5 to 12 parts of reinforcing agent, and 10 to 18 parts of flame retardant filler;
[0005] Component B is composed of the following components in parts by weight: 40-50 parts of vinyl siloxane, 10-18 parts of hydrogen-containing silicone oil, and 15-25 parts of anti-condensation hydrophobic filler;
[0006] The vinyl siloxane is obtained by the following method:
[0007] Low viscosity vinyl siloxane: 10W~20WmPa·s
[0008] High viscosity vinyl siloxane: 100W~200WmPa·s
[0009] Under a pH value of 6 to 7, the low-viscosity vinyl siloxane and the high-viscosity vinyl siloxane are mixed to obtain a vinyl siloxane having a viscosity of 60W to 80W mPa·s and a vinyl content of 0.01% to 0.05%;
[0010] Component C is composed of the following components by weight: 1.5 to 3 parts of leveling inhibitor; the leveling inhibitor is a polyether modified silicone leveling agent; the combination ratio is A: B: C = 1: 1: 0.5 to 1. The self-leveling fireproof and anti-condensation polymer material provided by this scheme controls the self-leveling time by adding component C, and then provides the corresponding self-leveling time according to the needs of the site to achieve the need for rapid curing; under the action of anti-condensation hydrophobic filler, the condensation generation in the electrical box and other parts is reduced; the reinforcing agent increases the physical stability of the material and is not easy to crack. The addition of flame-retardant filler has a fire-proof effect.
[0011] The hydrogen-containing silicone oil has a viscosity of 10 to 50 mPa·s and a hydrogen content of ≤1.55 ppm.
[0012] The catalyst is at least one of tetraethyl orthosilicate, ND-43, N-(2-aminoethyl)-3-aminopropyltriethoxysilane, and dibutyltin dilaurate;
[0013] The reinforcing agent is at least one of fumed silica, diatomaceous earth and calcium carbonate. The reinforcing agent provided in this solution is mainly used to increase the strength of the material, ensure the physical properties of the material in use, prevent cracking, and improve the plugging effect.
[0014] The flame retardant filler is at least one of ceramic powder, expanded carbon black, aluminum hydroxide, magnesium hydroxide, and glass fiber. The flame retardant filler provided in this solution is rapidly carbonized and forms a shell to prevent the flame from spreading after contacting the flame. In addition, some flame retardant fillers can be graded at high temperatures, have a high moisture content, and release moisture to reduce the temperature of the fire source, thereby extinguishing the fire, thereby improving the fire resistance of the material.
[0015] The anti-condensation hydrophobic filler is an ester compound prepared by reacting a terminal hydroxyl silica gel matrix compound with an acid anhydride or an acyl chloride under the catalysis of an organic base. The organic base is a tertiary amine.
[0016] The anti-condensation hydrophobic filler is an ester compound prepared by reacting epoxy-containing silica gel with diol ester under the catalysis of boron trifluoride. The anti-condensation hydrophobic filler makes use of the material characteristics to make the surface of the cured material rough and have a hydrophobic function to reduce the generation of condensation.
[0017] The leveling inhibitor: a variety of polyether-modified silicone leveling agents are synthesized and prepared by using double-terminal hydrogen-containing silicone oil, side-chain hydrogen polysiloxane and a variety of allyl polyether compounds under the action of platinum catalyst. The self-leveling time is controlled by inhibiting the content of the leveling agent, and different self-leveling times and curing times can be configured according to the needs of the site. The higher the content of the leveling inhibitor, the shorter the self-leveling time and curing time.
[0018] A method for preparing the self-leveling fireproof and anti-condensation polymer material as described above comprises the following steps:
[0019] (1) Take 40-50 parts of vinyl siloxane, add 5-12 parts of reinforcing agent, stir and mix thoroughly, add 10-18 parts of flame retardant filler, stir and mix evenly, add 1-3 parts of catalyst, continue to mix and stir evenly, use a planetary stirring kettle, vacuum stir for 15 minutes, and prepare component A;
[0020] (2) Take 40 to 50 parts of vinyl siloxane, add 15 to 25 parts of anti-condensation hydrophobic filler, stir evenly, add 10 to 18 parts of hydrogenated silicone oil, use a planetary stirring kettle, vacuum stir for 10 minutes, and prepare component B;
[0021] (3) Take 1.5 to 3 parts of leveling inhibitor to prepare component C;
[0022] (4) When using, directly mix them together in the ratio of A:B:C=1:1:0.5~1, stir evenly, and pour into the position that needs to be sealed.
[0023] Compared with the prior art, the present invention has at least the following beneficial effects: the self-leveling fireproof and anti-condensation polymer material provided by the present solution has controllable self-leveling time; after curing at room temperature, it has excellent flame retardancy and bonding strength, and good sealing effect; it has good moisture-proof, fireproof, and earthquake-resistant effects, and is not easy to age. Moreover, the cured plugging material can, through the porosity of its own material, meet the function of isolating water vapor under the action of anti-condensation hydrophobic filler, reduce condensation generation, and ensure the dryness of the internal environment after plugging; after the fire source appears, it contacts high temperature or burns, and the flame retardant material in the polymer material will quickly carbonize and form a crust to prevent the flame from spreading, and release a certain amount of water to reduce the combustion temperature, so that the polymer material can play an excellent fireproof role. Description of the drawings:
[0024] Figure 1 : Reaction diagram of vinyl siloxane and hydrogen-containing silicone oil under the action of catalyst. DETAILED DESCRIPTION
[0025] The technical solutions in the specific embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] Example 1
[0027] The present invention provides the following technical solution: a self-leveling fireproof and anti-condensation polymer material, which is composed of components A, B, and C; the combination ratio is A: B: C = 1: 1: 0.5. Component A is composed of the following components in parts by weight: 40 to 50 parts of vinyl siloxane, which is at least one of vinyl-terminated siloxane and vinyl-side siloxane, 1 to 3 parts of catalyst, which is at least one of tetraethyl orthosilicate, ND-43, N-(2-aminoethyl)-3-aminopropyltriethoxysilane, and dibutyltin dilaurate; 5 to 12 parts of reinforcing agent, which is 10 to 18 parts of at least one flame retardant filler selected from fumed silica, diatomaceous earth, and calcium carbonate; and the flame retardant filler is at least one of ceramic powder, expanded carbon black, aluminum hydroxide, magnesium hydroxide, and glass fiber. Component B is composed of the following components in parts by weight: 40 to 50 parts of vinyl siloxane and 10 to 18 parts of hydrogen-containing silicone oil, wherein the hydrogen-containing silicone oil has a viscosity of 10 to 50 mPa·s and a hydrogen content of ≤1.55 ppm.
[0028] 15 to 25 parts of anti-condensation hydrophobic filler; In this embodiment, the anti-condensation hydrophobic filler is an ester compound prepared by reacting a terminal hydroxyl silica gel matrix compound with an anhydride or an acyl chloride under the catalysis of an organic base, and the anhydride is selected from one of acetic anhydride, propionic anhydride, and butyric anhydride; acetic anhydride and propionic anhydride are further preferred; when the above-mentioned anhydrides are selected, the yield of the target product is more than 60%, and when acetic anhydride and propionic anhydride are selected, the reaction selectivity is higher, and the yield of the target product is more than 70%; the acyl chloride is selected from one of acetyl chloride, propionyl chloride, and butyryl chloride. The organic base is a tertiary amine, and the tertiary amine is selected from at least one of triethylamine, tripropylamine, and tributylamine, ensuring that the target product has a high yield and selectivity, and is cheap and easy to operate. In other embodiments, the anti-condensation hydrophobic filler is an ester compound prepared by reacting epoxy-containing silica gel with an ester of a diol under the catalysis of boron trifluoride.
[0029] The specific reaction process is: 10 parts of tetraethyl orthosilicate, 5 parts of methyltriethoxysilane, 120 parts of ethanol and 60 parts of water are stirred and hydrolyzed at a temperature of about 70°C for 1 to 2 hours. After cooling to room temperature, ammonia water is added to adjust the pH to 8 to 9. After standing for 24 hours, silica gel is obtained. Then 100 parts of silica gel are added to 100 parts of tetraethyl orthosilicate and 80 parts of ethanol, heated at 45°C, mixed evenly, and after 48 hours, cooled and dried to obtain a hydrophobic filler.
[0030] The vinyl siloxane is obtained by the following method: low-viscosity vinyl siloxane: 10W-20WmPa·s and high-viscosity vinyl siloxane: 100W-200WmPa·s, and under a pH value of 6-7, the low-viscosity vinyl siloxane and the high-viscosity vinyl siloxane are mixed to obtain a vinyl siloxane with a viscosity of 60W-80WmPa·s and a vinyl content of 0.01%-0.05%;
[0031] Component C is composed of the following components by weight: 1.5 to 3 parts of leveling inhibitor; the leveling inhibitor is a polyether-modified organic silicon leveling agent; the leveling inhibitor: a variety of polyether-modified organic silicon leveling agents are synthesized and prepared by using double-terminal hydrogen-containing silicone oil, side-chain hydrogen polysiloxane and various allyl polyether compounds under the action of platinum catalyst. The curing time is T1.
[0032] Example 2
[0033] The present invention provides the following technical solution: a self-leveling fireproof and anti-condensation polymer material, composed of components A, B, and C; the combination ratio is A: B: C = 1: 1: 0.8. Component A is composed of the following components in parts by weight: 40 to 50 parts of vinyl siloxane, which is at least one of vinyl-terminated siloxane or vinyl-side oxane, 1 to 3 parts of catalyst, which is at least one of tetraethyl orthosilicate, ND-43, N-(2-aminoethyl)-3-aminopropyltriethoxysilane, and dibutyltin dilaurate; 5 to 12 parts of reinforcing agent, which is 10 to 18 parts of at least one flame retardant filler selected from fumed silica, diatomaceous earth, and calcium carbonate; the flame retardant filler is at least one of ceramic powder, expanded carbon black, aluminum hydroxide, magnesium hydroxide, and glass fiber. Component B is composed of the following components in parts by weight: 40 to 50 parts of vinyl siloxane and 10 to 18 parts of hydrogen-containing silicone oil, wherein the hydrogen-containing silicone oil has a viscosity of 10 to 50 mPa·s and a hydrogen content of ≤1.55 ppm.
[0034] 15-25 parts of anti-condensation hydrophobic filler; in this embodiment, the anti-condensation hydrophobic filler is an ester compound prepared by reacting a hydroxyl-terminated silica gel matrix compound with an acid anhydride or an acyl chloride under the catalysis of an organic base. The organic base is a tertiary amine. In other embodiments, the anti-condensation hydrophobic filler is an ester compound prepared by reacting an epoxy-containing silica gel with an ester of a diol under the catalysis of boron trifluoride.
[0035] The vinyl siloxane is obtained by the following method: low-viscosity vinyl siloxane: 10W-20WmPa·s and high-viscosity vinyl siloxane: 100W-200WmPa·s, and in an environment with a pH value of 6-7, the low-viscosity vinyl siloxane and the high-viscosity vinyl siloxane are mixed to obtain a vinyl siloxane with a viscosity of 60W-80WmPa·s and a vinyl content of 0.01%-0.05%;
[0036] Component C is composed of the following components by weight: 1.5 to 3 parts of leveling inhibitor; the leveling inhibitor is an ether-modified organic silicon leveling agent; the leveling inhibitor: a variety of polyether-modified organic silicon leveling agents are synthesized and prepared by using double-terminal hydrogen-containing silicone oil, side-chain hydrogen polysiloxane and various allyl polyether compounds under the action of platinum catalyst. The curing time is T2.
[0037] Example 3
[0038] The present invention provides the following technical solution: a self-leveling fireproof and anti-condensation polymer material, which is composed of components A, B, and C; the combination ratio is A: B: C = 1: 1: 1. Component A is composed of the following components in parts by weight: 40 to 50 parts of vinyl siloxane, which is at least one of vinyl-terminated siloxane or vinyl-side oxane, 1 to 3 parts of catalyst, which is at least one of tetraethyl orthosilicate, ND-43, N-(2-aminoethyl)-3-aminopropyltriethoxysilane, and dibutyltin dilaurate; 5 to 12 parts of reinforcing agent, which is 10 to 18 parts of at least one flame retardant filler selected from fumed silica, diatomaceous earth, and calcium carbonate; and the flame retardant filler is at least one of ceramic powder, expanded carbon black, aluminum hydroxide, magnesium hydroxide, and glass fiber. Component B is composed of the following components in parts by weight: 40 to 50 parts of vinyl siloxane and 10 to 18 parts of hydrogen-containing silicone oil, wherein the hydrogen-containing silicone oil has a viscosity of 10 to 50 mPa·s and a hydrogen content of ≤1.55 ppm.
[0039] 15-25 parts of anti-condensation hydrophobic filler; in this embodiment, the anti-condensation hydrophobic filler is an ester compound prepared by reacting a hydroxyl-terminated silica gel matrix compound with an acid anhydride or an acyl chloride under the catalysis of an organic base. The organic base is a tertiary amine. In other embodiments, the anti-condensation hydrophobic filler is an ester compound prepared by reacting an epoxy-containing silica gel with an ester of a diol under the catalysis of boron trifluoride.
[0040] The vinyl siloxane is obtained by the following method: low-viscosity vinyl siloxane: 10W-20WmPa·s and high-viscosity vinyl siloxane: 100W-200WmPa·s, and in an environment with a pH value of 6-7, the low-viscosity vinyl siloxane and the high-viscosity vinyl siloxane are mixed to obtain a vinyl siloxane with a viscosity of 60W-80WmPa·s and a vinyl content of 0.01%-0.05%;
[0041] Component C is composed of the following components by weight: 1.5 to 3 parts of leveling inhibitor; the leveling inhibitor is an ether-modified organic silicon leveling agent; the leveling inhibitor: a variety of polyether-modified organic silicon leveling agents are synthesized and prepared by using double-terminal hydrogen-containing silicone oil, side-chain hydrogen polysiloxane and various allyl polyether compounds under the action of platinum catalyst. The curing time is T3.
[0042] Serial number T1 T2 T3 Time (min) 60 50 40
[0043] Table 1: Curing time data of Examples 1-4;
[0044] It can be seen from Table 1 that the self-leveling time and curing time are inversely correlated with component C. The higher the content of component C, the shorter the self-leveling time. The content of component C can be determined according to the construction needs on site; the operation is simple, efficient, and can adapt to different working environments.
[0045] Example 4
[0046] A method for preparing a self-leveling fireproof and anti-condensation polymer material comprises the following steps:
[0047] (1) Take 40-50 parts of vinyl siloxane, add 5-12 parts of reinforcing agent, stir and mix thoroughly, add 10-18 parts of flame retardant filler, stir and mix evenly, add 1-3 parts of catalyst, continue to mix and stir evenly, and stir in a planetary stirring kettle under vacuum for 15 minutes to prepare component A;
[0048] (2) Take 40-50 parts of vinyl siloxane, add 15-25 parts of anti-condensation hydrophobic filler, stir evenly, add 10-18 parts of hydrogenated silicone oil, and stir in a planetary stirring kettle under vacuum for 10 minutes to prepare component B;
[0049] (3) Take 1.5 to 3 parts of leveling inhibitor to prepare component C;
[0050] (4) When using, directly mix them together in the ratio of A:B:C=1:1:0.5~1, stir evenly, and pour into the position that needs to be sealed.
Claims
1. A self-leveling fireproof and anti-condensation polymer material, characterized in that: It is composed of components A, B and C; Component A is composed of the following components in parts by weight: 40-50 parts of vinyl siloxane, 1-3 parts of catalyst, 5-12 parts of reinforcing agent, and 10-18 parts of flame retardant filler; Component B is composed of the following components in parts by weight: 40-50 parts of vinyl siloxane, 10-18 parts of hydrogen-containing silicone oil, and 15-25 parts of anti-condensation hydrophobic filler; The vinyl siloxane is obtained by the following method: Low viscosity vinyl siloxane: 10W~20WmPa·s High viscosity vinyl siloxane: 100W~200WmPa·s Under a pH value of 6 to 7, the low-viscosity vinyl siloxane and the high-viscosity vinyl siloxane are mixed to obtain a vinyl siloxane having a viscosity of 60W to 80W mPa·s and a vinyl content of 0.01% to 0.05%; Component C is composed of the following components in parts by weight: 1.5 to 3 parts of a leveling inhibitor; the leveling inhibitor is a polyether-modified organic silicon leveling agent; The combination ratio is A:B:C=1:1:0.5~1.
2. The self-leveling fireproof and anti-condensation polymer material according to claim 1, characterized in that: The hydrogen-containing silicone oil has a viscosity of 10 to 50 mPa·s and a hydrogen content of ≤1.55 ppm.
3. The self-leveling fireproof and anti-condensation polymer material according to claim 1, characterized in that: The catalyst is at least one of tetraethyl orthosilicate, ND-43, N-(2-aminoethyl)-3-aminopropyltriethoxysilane and dibutyltin dilaurate.
4. The self-leveling fireproof and anti-condensation polymer material according to claim 1, characterized in that: The reinforcing agent is at least one of fumed silica, diatomaceous earth and calcium carbonate.
5. The self-leveling fireproof and anti-condensation polymer material according to claim 1, characterized in that: The flame retardant filler is at least one of ceramic powder, expanded carbon black, aluminum hydroxide, magnesium hydroxide and glass fiber.
6. The self-leveling fireproof and anti-condensation polymer material according to any one of claims 1 to 5, characterized in that: The anti-condensation hydrophobic filler is an ester compound prepared by reacting a terminal hydroxyl silica gel matrix compound with an acid anhydride or an acyl chloride under the catalysis of an organic base.
7. The self-leveling fireproof and anti-condensation polymer material according to claim 6, characterized in that: The organic base is a tertiary amine.
8. The self-leveling fireproof and anti-condensation polymer material according to any one of claims 1 to 5, characterized in that: The anti-condensation hydrophobic filler is an ester compound prepared by reacting epoxy-containing silica gel with diol ester under the catalysis of boron trifluoride.
9. The self-leveling fireproof and anti-condensation polymer material according to any one of claims 1 to 5, characterized in that: The leveling inhibitor is prepared by synthesizing a variety of polyether-modified organic silicon leveling agents by using double-terminal hydrogen-containing silicone oil, side-chain hydrogen polysiloxane and a variety of allyl polyether compounds under the action of platinum catalyst.
10. A method for preparing the self-leveling fireproof and anti-condensation polymer material according to claim 1, characterized in that: The steps include: (1) Take 40-50 parts of vinyl siloxane, add 5-12 parts of reinforcing agent, stir and mix thoroughly, add 10-18 parts of flame retardant filler, stir and mix evenly, add 1-3 parts of catalyst, continue to mix and stir evenly, and vacuum stir for 15 minutes to prepare component A; (2) Take 40-50 parts of vinyl siloxane, add 15-25 parts of anti-condensation hydrophobic filler, stir evenly, add 10-18 parts of hydrogenated silicone oil, stir in vacuum for 10 minutes, and prepare component B; (3) Take 1.5 to 3 parts of leveling inhibitor to prepare component C; (4) When using, directly mix them together in the ratio of A:B:C=1:1:0.5~1, stir evenly, and pour into the position that needs to be sealed.